«Dastūr Al-‘Ilāj» medical treaty and its manuscripts - Shadkam, Z.; Tuyakbayev, O.O.; Kydyrbayeva, U.T.; Abdrakhanov, D.M. (Journal of Oriental Studies, 2021)
Among the historical texts written in medieval Arabic letters found in the modern Kazakh steppes, there are many records related to medicine. They are sometimes found in the form of short texts at the beginning or at the beginning of a few pages of notebooks, sometimes as part of a book, and sometimes as a complete medical record book for treatment. These historical texts, which are the common heritage of Turkic and world civilization, play an important role in recognizing, knowing and understanding the steppe civilization, the Kazakh language, customs and traditions to determine the system of history of beliefs. Medicinal works written in the Chagatai language in the Middle Ages have been little studied in domestic science for various reasons. Research does not exceed the size of the article. In the article we try to give a comfortable information about the medicine of the steppe civilization, nomads, reviewing the author, language and versions of the medical work "Dastur al-‘ilāj", written in the first half of the XVI century.